The philosophy of Total Quality Management for the environment - العنزي سعد; العبيد عائشة حمودي (Journal of Economics and Administrative Sciences, 2009)
The Environmental Management System (EMS) is an important foundation for effective control of the organization’s outstanding environmental performance. It applies standards for substantive review and provides a structure and a way to apply it in all aspects of the work, In order to ensure full compliance with environmental requirements, legislation and laws that are consistent with the wishes and aspirations of society. Industrial activities are one of the main sources affecting the surrounding environment through the generation of pollutants and industrial wastes on different types of gas, liquid and solid. Therefore, it can not be said that an industry is quality without environmental control. This is why organizations should pay attention to Total Quality Environment Management (TQEM), as they have characteristics and characteristics that need to be considered and adequately understood, since they provide a lot of production and operations costs, Products and services of an environmentally and industrial quality, so that they can benefit greatly in the field of competition, gain profits, increase market share, and future expansion as well. The aim of this research paper is to enable researchers, practitioners and interested persons to familiarize themselves with the philosophy of TQM for the environment, with all the concepts, elements, tools, effects and mechanisms to be implemented in order to implement the correct applications at the level of the industrial organization. In implementing this philosophy appropriately. عرض المزيد عرض أقل